PENGARUH PROMOSI, KEMUDAHAN PENGGUNAAN, KEPERCAYAAN KONSUMEN DAN KUALITAS INFORMASI TERHADAP MINAT BELI DI SITUS BUKALAPAK (Pada Mahasiswa Universitas Diponegoro) - Widhiani, Asterina; Idris, Idris (Diponegoro Journal of Management, 2018)
The purpose of this study is to analyze whether there is influence of promotion, ease of use, consumer trust and quality of information on buying interest in Bukalapak online sale site. The sampling technique used in this research is purposive sampling approach, that is College Students of Diponegoro University who have accessed Bukalapak website but have never made a purchase. The sample used is as much as 100 respondents.The sampling technique used in this research is purposive sampling approach, that is College Students of Diponegoro University who have accessed Bukalapak website but have never made a purchase. The sample used is as much as 100 respondents. The data were collected by using questionnaires. The analysis method used is multiple regression analysis and the operation uses SPSS version 22.The results showed that promotion, ease of use, consumer confidence and quality of information have a positive influence on buying interest in Bukalapak online sale site. Information quality  became  the  highest  influence  in  this  research.  and  consumer  trust,  ease  of  use  and promotion sequentially have the highest influence in this study after the quality of information